2007
DOI: 10.1159/000100999
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glucose-Free Dialysis Solutions on Human Peritoneal Mesothelial Cells

Abstract: Background: Glucose-free dialysis solutions may be more biocompatible owing to the physiological pH and the lack of glucose degradation products, and the effects can be reflected by the changes in some markers of peritoneal mesothelial cells (PMC). Method: Peritoneal effluents were collected in 17 CAPD patients after one daily exchange of glucose-containing dialysate to Nutrineal (1.1% amino acid-based PDF), and human PMC were cultured from peritoneal effluent and treated with various peritoneal dialysis (PD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…The finding of the study reported here that exposure to Aminobic did not affect HSP-72 response and did not acutely impair HPMC viability points to improved biocompatible profile of the solution. At first glance, these data appear to be in line with those of Chang et al [24], who also found no up-regulation of HSP in response to amino-acid solution. Surprisingly, however, these authors also found no significantly increased expression of HSP in cells exposed to the conventional PD solution with acidic pH and high GDP contents.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The finding of the study reported here that exposure to Aminobic did not affect HSP-72 response and did not acutely impair HPMC viability points to improved biocompatible profile of the solution. At first glance, these data appear to be in line with those of Chang et al [24], who also found no up-regulation of HSP in response to amino-acid solution. Surprisingly, however, these authors also found no significantly increased expression of HSP in cells exposed to the conventional PD solution with acidic pH and high GDP contents.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, the incubation of cells with Aminobic resulted in a significant increase in unstimulated IL-6 secretion. A similar effect has been reported by Chang et al [24]. Plum et al [31] and Martikainen et al [32] who detected increased intraperitoneal levels of IL-6 in patients receiving amino-acid-based solutions and linked this effect to better preservation of HPMC.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In our observational study, a cause-effect relationship cannot be established. The data on dialysis effectivity (Kt/v), type of peritoneum ("slow transporters", "fast transporters") and dialysis regime were not recorded, and especially the influence of the use of icodextrin or non-glucose based peritoneal dialysis solution (Nutrineal) on glycemic variability would have been of interest to delineate [37][38][39][40][41]. Furthermore, data on peritonitis as a complication of PD, which can affect ultrafiltration and glucose absorption [42], were not available in the present study.…”
Section: Plos Onementioning
confidence: 99%